2014
DOI: 10.1001/jama.2013.278795
|View full text |Cite|
|
Sign up to set email alerts
|

Pain at 12 Months After Surgery for Breast Cancer

Abstract: Persistent pain following breast cancer treatments remains a significant clinical problem despite improved treatment strategies. 1 Data on factors associated with persistent pain are needed to develop prevention and treatment strategies and to improve the quality of life for breast cancer patients. This prospective study examined the prevalence and severity of and the factors associated with chronic pain after breast cancer surgery and adjuvant treatments. Methods | Consecutive patients younger than 75 years w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
90
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 6 publications
11
90
3
3
Order By: Relevance
“…26,35 Whether or not we incorporated missing data for nonsignificant predictors or converted categorical data for age and BMI to continuous data (Appendix 13, available at www.cmaj.ca/lookup/suppl/ doi:10.1503/cmaj.151276/-/DC1) did not appreciably influence the results. 42 Wilson et al, 2013 49 Mejdahl et al, 2013 26 Johansen et al, 2014 52 Lundstedt et al, 2012 41 De Oliveira et al, 2014 37 Steegers et al, 2008 44 Meretoja et al, 2014 58 Yang et al, 2010 51 Tasmuth et al, 1997 46 Shahbazi et al, 2015 60 Husen et al, 2006 40 Bell et al, 2014 59 Swenson et al …”
Section: Subgroup Analyses Meta-regression and Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…26,35 Whether or not we incorporated missing data for nonsignificant predictors or converted categorical data for age and BMI to continuous data (Appendix 13, available at www.cmaj.ca/lookup/suppl/ doi:10.1503/cmaj.151276/-/DC1) did not appreciably influence the results. 42 Wilson et al, 2013 49 Mejdahl et al, 2013 26 Johansen et al, 2014 52 Lundstedt et al, 2012 41 De Oliveira et al, 2014 37 Steegers et al, 2008 44 Meretoja et al, 2014 58 Yang et al, 2010 51 Tasmuth et al, 1997 46 Shahbazi et al, 2015 60 Husen et al, 2006 40 Bell et al, 2014 59 Swenson et al …”
Section: Subgroup Analyses Meta-regression and Sensitivity Analysesmentioning
confidence: 99%
“…36,39,43,50,53,55,56 However, the results from these studies were consistent with the results from studies amenable to pooling. We used the IASP criteria for the definition of persistent pain in this review; however, 14 of the included studies did not report whether their assessment of persistent postsurgical pain excluded other causes of pain; 26,[33][34][35][36]43,45,47,48,50,51,54,56,58 as such, they may have overestimated the prevalence of persistent pain.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…12 Several studies have indicated that psychological comorbidity is a risk factor for PPBCT, 1,13 with recent prospective studies indicating a correlation between preoperative psychological symptoms and PPBCT. 3,4,14,15 A prevalence of preoperative depression of 37% and anxiety of 70% has been reported among patients with breast cancer, 16 whereas the prevalence of severe psychological distress has been reported to be around 40%. [17][18][19] Longitudinal studies suggest a reciprocal relationship between depression and pain, 20,21 in that depression may lead to pain and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…13 Ameliyat öncesi ağrı ve ameliyat sonrası akut ağrı, ameliyat sonrası uzun dönemde gelişebilen kronik ağrı sendromlarında önemli risk faktörleri olarak tanımlanmaktadır. Ayrıca, ameliyat sonrası akut ağrının azaltılması sonucu, ameliyat sonrası kronik ağrı gelişme riskinin azaltılabileceği düşü-nülmektedir.…”
unclassified
“…Ayrıca, ameliyat sonrası akut ağrının azaltılması sonucu, ameliyat sonrası kronik ağrı gelişme riskinin azaltılabileceği düşü-nülmektedir. [12][13][14][15][16][17] Bu nedenle akut ağrı yönetimi; bireyin cerrahi sonrası iyileşme süresinin kısaltılması, tedavi maliyetinin azaltılması, kronik ağrı oluşumunun önlen-mesi ve yaşam kalitesinin artırılması açısından önemlidir. Ağrı yönetiminde farmakolojik ajanlar ile birlikte gevşeme egzersizleri, sıcak-soğuk uygulama, aromaterapi, akapunktur, refleksoloji, masaj gibi nonfarmakolojik uygulamaların meme cerrahisi sonrası ağrı yönetiminde kullanılması önerilmek-tedir.…”
unclassified